Nearest Metempsychosis in the Cinderella Fairy-Tale (Proceedings of Southern Federal University. Philology, 2021)
DOI 10.18522/1995-0640-2021-3-87-101The article describes functional mechanism of heroine’s metempsychosis in the Oriental and Occidental Cinderella fairy-tale. According to the classification of Aarne - Thompson, these tales belong to the type 510 A “persecution of the heroine”, which is associated with a complex of other plots (510 B, 511, 511 A). We limit our research only to those tales in which the identification of the heroine occurs by the shoe. The origins of this literature phenomenon are disclosed in terms of religious conception and traditional believes of the representatives of the thai-kadai language group (IX-XIX centuries). For analysis the Zhuang, Thai and Lao versions of Cinderella fairy-tale were taken, the ritual and mythological aspect of fairytale narrative is disclosed on the material base. The article also describes functions of ancestors’ cult and discusses totemic attitude of the people of the East and South-East Asia in the functioning system of the oriental fairytale which all together form the metempsychosis conception. On the ground of the ethnographic data the author substantiates the choice of animal and plants (namely, a bird/parakeet, bamboo, quince tree, hazel, palm tree, dove) which were used for the sequence of character’s incarnations in the tales. If in oriental tales the heroine’s soul is transmigrated into animals and plants, in Western European fairy tales the heroine is transformed thanks to the help of a plant or bird - the reincarnations of her mother. Only Ch. Perrault, following the rationalistic spirit of the times, does not use metempsychosis directly, but his tale also contains transformations of the inanimate into the animate: plants and animals turn into coachmen and lackeys.The metempsychosis’ final aims of the magic fairy-tales are formulated. An appeal to the European tradition (Basile “The Cat Cinderella”, 1634; Perrault “Cinderella”, 1697; the Brothers Grimm “Cinderella”, 1812), in which metempsychosis is partially preserved, confirms the eastern origin of the tale and allows a deeper understanding of its folkloric origins.Key words: Cinderella, oriental fairy-tale, folkloric origins, metempsychosis, totem.